A pathogen complex between the root knot nematode Meloidogyne incognita and Fusarium verticillioides results in extreme mortality of the inka nut (Plukenetia volubilis) - Guerrero Abad, Juan Carlos; Padilla Domínguez, Ammer; Torres Flores, Elías; López Rodríguez, Carlos; Guerrero Abad, Roger Arbildo; Coyne, Danny; Oehl, Fritz; Corazon Guivin, Mike Anderson (Julius Kühn-Institut., 2021)
The combined infection of the root knot nematode Meloidogyne incognita and two Fusarium species led to high plant mortality of inka nut (Plukenetia volubilis) seedlings in pots after 80 days growth in two independent inoculation experiments. Inoculation of M. incognita juveniles and conidia of F. solani or F. verticillioides, simultaneously, increased plant mortality by 25-30%, compared with M. incognita alone (5-10% mortality). When inoculated with F. verticillioides at 20 days post nematode inoculation, plant mortality increased to 55%. Either of the Fusarium spp. alone caused some plant mortality, but less than when combined with M. incognita. The synergistic interaction of M. incognita and especially F. verticillioides demonstrates a lethal outcome for inka nuts. It appears that M. incognita creates favorable conditions that lead to enhanced effect and damage by the Fusarium species, especially F. verticillioides, leading to devastating levels of plant death.